Advances in affective and pleasurable design : proceedings of the AHFE 2016 International Conference on Affective and Pleasurable Design, July 27-31, 2016, Walt Disney World, Florida, USA /: proceedings of the AHFE 2016 International Conference on Affective and Pleasurable Design, July 27-31, 2016, Walt Disney World, Florida, USA. ([2016]) - Unknown
No abstract available